Delivering behavioural change at scale: What conservation can learn from other fields. (May 2021) - Travers, Henry; Walsh, James; Vogt, Sonja; Clements, Tom; Milner-Gulland, E.J.
Abstract: Developing interventions to change human behaviour at scale is critical to achieving the new Global Biodiversity Framework goals. One strategy that conservation practitioners can adopt in pursuing this ambition is to look for lessons from other fields engaged in sustainable development, such as development economics and behavioural science. Over the past twenty years, these fields have generated a large and growing evidence-base of strategies for improving key sustainability indicators in areas such as health, livelihoods and education. This empirical revolution has been accelerated by rapid advances in understanding the social and psychological foundations of human behaviour. In this paper, we identify three areas that can help conservation to bring behaviour change programmes to scale. First, conservation practitioners should develop expertise in human behaviour developed in the social and cognitive sciences. Second, conservation researchers should adopt empirical methods widely practiced in development economics to rigorously identify whether, how and why interventions work. Third, conservation should integrate with the policy institutions and systems to facilitate learning and scaling. Highlights: Conservation should look to learn lessons from other fields of public policy. Interventions must take account of the psychological foundations of behaviour. Conservation policymaking should be informed by a rigorous evidence base. New institutions and systems are required to achieve change at scale. An ethical approach to adopting conservation behavioural programmes is required.